An Over-View of Tuberculosis of Female Genital Tract With Reference To Experience in a Medical College in Rural Set-Up in West Bengal: A Retrospective Two Year Study - Datta, J; Ghosh, TK; Ghosh, S; Guha, D (Bangladesh Journal of Medical Science, 2012)
Aim: To determine frequency of female genital tract (FGT) tuberculosis (TB) in the gynecological biopsies received in the Department of pathology of a peripheral medical college. Methods: This is a retrospective study conducted in the Department of Pathology of Burdwan Medical College & Hospital. Histopathological records of two year (2008-2010) were retrieved and searched for the cases of female genital tract TB. Relevant histopathological findings and clinical data were recorded and analyzed. Results: There were 1537 cases of gynecological biopsy and 9 cases were diagnosed as FGT tuberculosis based on histopathological and clinical findings. Ovarian benign cystic teratoma was seen in one case along with ipsilateral tuberculous salpingitis, one case showed B/L ovarian tuberculosis with involvement of both the tubes. Bilateral fallopian tubes were involved in 2 cases and endometrial tuberculosis was diagnosed in 5 cases with 1 case showing simultaneous involvement of the cervix. In one case omental biopsy received along with tubal specimen showed tuberculous granulomas. Conclusion: FGT tuberculosis was usually seen in age 16-28 years and constituted 0.59% of total gynecological cases. Fallopian tubes, ovaries and endometrium and cervix were affected with the involvement of peritoneum or omentum, commonest being tuberculous endometritis. Histopathology, in association with clinical findings still remains gold standard for the diagnosis of FGT tuberculosis in our country despite advancement in diagnostic modalities; however, incidental histological detection in clinically unanticipated cases is not an uncommon event. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11719 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12